Governance and Reforms of Banking System In India: A study on the governance and reforms of the banking system in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Strengthening financial systems has been one of thecentral issues facing emerging markets and developing economies. This isbecause sound financial systems serve as an important channel for achievingeconomic growth through the mobilization of financial savings, putting  them to productive use and transformingvarious risks (Beck,  Levin and Loayza1999;  King  and Levin 1993;  Rajan and Zingales 1998;  Demirgüç-Kunt, Asli  and Maksimovic  1998;  Jayaratne and  Strahan  1996). Many countries adopted a  series of financial sector liberalizationmeasures in the late 1980s and early 1990s that included  interest  rate liberalization,  entry  deregulations,  reduction of  reserve requirements  and removal of credit allocation. In manycases, the timing of financial sector liberalization coincided with that ofcapital account liberalization. Domestic banks were given access to cheap loansfrom abroad and allocated those resources to domestic production sectors.